Tiao-Bu-Fei-Shen Formula Improves Glucocorticoid Resistance of Chronic Obstructive Pulmonary Disease via Downregulating the PI3K-Akt Signaling Pathway and Promoting GRα Expression. (11th February 2023) - Zhou, Pengcheng; Ma, Jianli; Yu, Wei; Chen, Keling; Zhang, Wensheng; Zhou, Jiang
Abstract : Objective . To predict and determine the mechanism through which Tiao-Bu-Fei-Shen (TBFS) formula improves glucocorticoid resistance in chronic obstructive pulmonary disease (COPD), using network pharmacology, molecular docking technology, and in vitro studies. Methods . The main active components and associated targets of TBFS were screened using the systems pharmacology database of traditional Chinese medicine database (TCMSP). The main COPD targets were retrieved from the Human Gene (GeneCards) and DrugBank databases. A protein-protein interaction (PPI) network was constructed using the protein interaction platform STRING and Cytoscape 3.6.1. Gene ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genome Pathway (KEGG) analyses were performed using the biological information annotation database Metascape. Molecular docking was performed using the AutoDock Vina software. THP-1 monocytes were treated with TBFS-containing serum and cigarette smoke extract (CSE) for 48 h, and cell proliferation in each group was determined using cell counting kit-8 (CCK-8). A COPD cell model was constructed by stimulating THP-1 monocytes with CSE for 12 h. A lentivirus vector for RNA interference of histone deacetylase 2 (HDAC2) gene was constructed and transfected into the THP-1 monocytes, and the transfection efficiency was verified using quantitative polymerase chain reaction (qPCR) and western blotting (WB). The expression of HDAC2 in each group of cells was detected using qPCR, and the expression of HDAC2, phosphoinositide-3 kinase (PI3K) p85 α, glucocorticoid receptor α (GR α ), and P-AKT1 in each group of cells was detected through WB. Results . A total of 344 TBFS active components, 249 related drug targets, 1, 171 COPD target proteins, and 138 drug and disease intersection targets were obtained. Visual analysis of the PPI network map revealed that the core COPD targets of TBFS were AKT1, IL-6, TNF, TP53, and IL1- β . KEGG pathway enrichment analysis resulted in the identification of 20 signaling pathways as the main pathways involved in the action of TBFS against COPD, including the PI3K-Akt, TNF, and IL-17 signaling pathways. Molecular docking experiments revealed a strong binding capacity of kaempferol, luteolin, and quercetin to the ATK1 protein in TBFS, with quercetin performing the best. PCR results showed that treatment with TBFS significantly increased the expression levels of HDAC2 in the COPD model. WB results showed that TBFS treatment significantly increased the expression levels of GR α and HDAC2 in the COPD model, while reducing the expression levels of P-AKT1. Conclusion . TBFS treatment improves glucocorticoid resistance observed in COPD through downregulation of the PI3K-Akt signaling pathway and promotion of GR α expression.